2016
DOI: 10.1097/txd.0000000000000578
|View full text |Cite
|
Sign up to set email alerts
|

Deep Vein Thrombosis and Pulmonary Embolism in Liver Transplant Patients

Abstract: IntroductionDeep vein thrombosis (DVT) and pulmonary embolism (PE) are surgical complications estimated to occur in 5% to 10% of patients. There are limited data regarding DVT/PE in the early postoperative period in liver transplant patients. The aim of this study is to determine risk factors that influence the incidence of DVT/PE and the effectiveness of prophylaxis.MethodsWe reviewed the records of 999 patients who underwent initial liver transplant between January 2000 and June 2012 at Henry Ford Hospital. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 62 publications
1
34
0
Order By: Relevance
“…Liver transplantation (LT) is the only longterm therapy for patients with cirrhosis. This complex procedure is still fraught with hemorrhage and thrombosis . In this retrospective study, we report the association of abnormal fibrinolysis phenotypes with poorer outcomes during and after LT.…”
mentioning
confidence: 94%
“…Liver transplantation (LT) is the only longterm therapy for patients with cirrhosis. This complex procedure is still fraught with hemorrhage and thrombosis . In this retrospective study, we report the association of abnormal fibrinolysis phenotypes with poorer outcomes during and after LT.…”
mentioning
confidence: 94%
“…However, a growing body of evidence has established that patients with cirrhosis and those after liver transplantation may actually demonstrate a hypercoagulative state during and after the transplant procedure [28]. As complex and unpredictable in onset and severity, a few risk factors for venous thromboembolism after liver transplantation were identified, for example, prolonged immobilization, administration of excessive procoagulant factors, and peripherally inserted central catheter lines [14,15]. Other factors involved defects in the proteins that normally regulated anticoagulation, such as protein C, protein S, and antithrombin deficiency, transmitted from donors to recipients [29][30][31][32], and this can be missed Similarly, kidney and heart transplant recipients have been reported to be at risk of venous thromboembolism as mentioned previously [16,18,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…These reports showed incidences varying between 4.5 and 8.6%. [80][81][82][83][84] Notably, the study that reported an incidence of 8.6% only considered the number of deep vein thrombosis, 82 an even higher incidence would likely have been found if pulmonary embolisms had been taken into account. Importantly, none of the patients in this study received pharmacological thromboprophylaxis.…”
Section: Liver Transplantationmentioning
confidence: 99%